CD44 Expression Profile Varies According to Maturational Subtypes and Molecular Profiles of Pediatric T-Cell Lymphoblastic Leukemia - Marques, Luísa Vieira Codeço; Noronha, Elda Pereira; Andrade, Francianne Gomes; Santos-Bueno, Filipe Vicente dos; Mansur, Marcela B.; Terra-Granado, Eugenia; Pombo-de-Oliveira, Maria S. (Frontiers in Oncology, 2018)
CD44 is a glycoprotein expressed in leucocytes and a marker of leukemia-initiating cells, being shown to be important in the pathogenesis of T cell acute lymphoblastic leukemia (T-ALL). In this study, we have (i) identified the aberrant antigenic pattern of CD44 and its isoform CD44v6 in T-ALL; (ii) tested the association with different T-cell subtypes and genomic alterations; (iii) identified the impact of CD44 status in the T-ALL outcome. Samples from 184 patients (123 T-ALL and 61 AML; <19 years) were analyzed throughout multiparametric flow cytometry. Mutations in N/KRAS, NOTCH1, FBXW7 as well as STIL-TAL1 and TLX3 rearrangements were detected using standard molecular techniques. CD44 expression was characterized in all T-ALL and AML cases. Compared with AML samples in which the median fluorescence intensity (MFI) was 79.1 (1-1272), T-ALL was relatively low, with MFI 43.2 (1.9-1239); CD44v6 expression was rarely found, MFI 1 (0.3-3.7). T-ALL immature subtypes (mCD3/CD1aneg) had a lower CD44 expression, MFI 57.5 (2.7-866.3), whereas mCD3/TCRγδpos cases had higher expressions, MFI 99.9 (16.4-866.3). NOTCH1mut and STIL-TAL1 were associated with low CD44 expression, whereas N/KRASmut and FBXW7mut cases had intermediate expression. In relation to clinical features, CD44 expression was associated with tumor infiltrations (p=0.065). However, no association was found with initial treatment responses and overall survival prediction. Our results indicate that CD44 is aberrantly expressed in T-ALL being influenced by different genomic alterations. Unraveling this intricate mechanism is required to place CD44 as a therapeutic target in T-ALL.